2018
DOI: 10.31189/2165-6193-7.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Prescription Techniques in Cardiac Rehabilitation Centers in Midwest States

Abstract: Introduction: Cardiac rehabilitation (CR) is a primary prescribed treatment for a variety of cardiovascular disease states, including: coronary artery disease, percutaneous coronary intervention (PCI), coronary artery bypass graft (CABG), myocardial infarction (MI), and heart failure. For this reason, exercise prescription guidelines for cardiac patients have been established. However, it is unclear how these guidelines are being administered at cardiac rehabilitation centers. The purpose of this study is to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 19 publications
(18 reference statements)
2
23
2
1
Order By: Relevance
“…The progression of exercise is typically not standardized from one CR center to another, so comparison between different healthcare systems should be done with caution [6,16]. Several vague recommendations for exercise progression have been published, and include a gradual increase in RPE from 1 to 5 units beyond 13 (6–20 scale) per session as tolerated [17]; a systematic increase in exercise duration, frequency, and intensity [14]; and an increase in exercise duration prior to an increase in intensity [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The progression of exercise is typically not standardized from one CR center to another, so comparison between different healthcare systems should be done with caution [6,16]. Several vague recommendations for exercise progression have been published, and include a gradual increase in RPE from 1 to 5 units beyond 13 (6–20 scale) per session as tolerated [17]; a systematic increase in exercise duration, frequency, and intensity [14]; and an increase in exercise duration prior to an increase in intensity [18].…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, exercise programming in CR should be focused on improving exercise capacity. However, a recent survey study among CR facilities found that nearly 60% of clinics reported no defined goals for improving exercise capacity among patients [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This helps clinical exercise physiologists establish ischemic thresholds that should not be exceeded during exercise training in order to avoid eliciting ischemia. Despite this approach being the gold standard for exercise programming in CR [5,6], in a recent survey study among CR clinics in the United States it was reported that only 33% of clinics conduct baseline GXTs [7]. A similar survey of forty-five Dutch clinics identified that 36% of heart failure patients, and 30% of coronary artery disease patients did not perform a baseline GXT prior to beginning CR [8].…”
Section: Introductionmentioning
confidence: 99%
“…Однако в ру тинной практике перечисленные нагрузочные тесты выполняются не часто, в т. ч. перед включением больного в программу КР. Анализ реальной практики 56 реабилитационных клиник в 6 штатах США показал выполнение нагрузочного теста (ВЭМ или тредмиле) перед началом КР только у 34% больных [4]. Снижение частоты применения нагрузочных проб объясняли разными причинами: сокращением сроков госпитализации, совершенствованием методов диагностики, достижением полной реваскуляризации миокарда, противопоказаниями больного и даже личными предпочтениями врачей.…”
unclassified